Study of Vehicle-to-Grid Interaction Income Considering Scenario Coefficient - Hongbo CHENG; Yuanxi GUO; Zixuan SHANG; Yunxiao LI (Zhongguo dianli)
As the urgency degree of the grid demand for power varies due to the dynamic change of the grid, the income generated by vehicle-to-grid (V2G) interaction also differs under different urgency degrees. To achieve a more reasonable distribution of the interaction income, this paper proposed a distribution method of the V2G interaction income that considers the difference in the power grid scenario. The scenario coefficient is used to reflect the urgency degree of the grid demand for power, and equivalent substitution of ancillary services is discussed to analyze the V2G interaction income. The response probability of electric vehicle users under different electricity prices is taken into account and an improved bargaining game model is built to solve the electricity price for the optimal scenario response and thereby obtain the income distribution shares of the two sides participating in the V2G interaction. The effectiveness and superiority of the proposed income distribution model are verified through the comparative case analysis of the load reduction degree, income, and fair entropy of the distribution method among several response strategies.